Poromechanics V 2013
DOI: 10.1061/9780784412992.124
|View full text |Cite
|
Sign up to set email alerts
|

Porosity and Permeability Change under Stress and Correlation to Rock Texture

Abstract: Laboratory experiments and numerical simulations were used to study the effect of pore structure on stress-porosity-permeability relations. It has been hypothesized that heterogeneous multi-porosity system with the permeability-controlling porosity more compressible than the other porosities would demonstrate a high stress-sensitivity in the permeability. The porosity and permeability of carbonate, sandstone, and fractured cores were measured under isostatic stress conditions. A power law was used to correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…This agreement indicates that stress sensitivity of porosity and absolute permeability of our medium is mostly similar to those of an idealized capillary tube bundle and the tight sandstones previously studied. [19,20]. Pore throats or fractures that control the overall permeabilities of cores only contribute to a small fraction of the net porosity.…”
Section: Absolute Permeability Under Stressmentioning
confidence: 99%
See 3 more Smart Citations
“…This agreement indicates that stress sensitivity of porosity and absolute permeability of our medium is mostly similar to those of an idealized capillary tube bundle and the tight sandstones previously studied. [19,20]. Pore throats or fractures that control the overall permeabilities of cores only contribute to a small fraction of the net porosity.…”
Section: Absolute Permeability Under Stressmentioning
confidence: 99%
“…Experimental results showed that + in fractured rocks are higher than those in carbonates, which in turn are higher than those in sandstones [20]. It was pointed out that pore throats are more stress sensitive than pore bodies, which would lead to larger values of + [21].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations